Simulasi Pembayaran Menggunakan RFID (Radio Frequency Identification) Pada Studi Kasus Layanan Mahasiswa - Alvin Santoso; Henry Novianus Palit; Alexander Setiawan (Jurnal Infra, 2019)
Money is a tool for transactions. The growing of technology make payment methods is also more varied, for example with e-money. However, even there are methods like this, administrative Petra Christian University activities still use manual system so that make less practical. When e-money going to applied, there is a security aspect that must be considered. One of them is how to secure the balance that is on the card so that the balance cannot be duplicated.To make e-money payment on administrative Petra Christian University there will be make payment system with RFID (Radio Frequency Identification) with money in the card. There are 3 methods, AES, DES, 3DES with CBC and CFB mode in comparison of the speed encryption decryption, memory usage, and anti-duplication on the card. Besides there will be comparison of speed when doing top up/withdrawl balance/transaction when money stored in card and money stored in database.The test results found that there anti-duplication method successfully applied, encryption decrytion speed AES, DES, 3DES mode CBC more faster than CFB and memory usage same with all of method. Money in database have a faster process in top up/withdrawl balance while DES with CBC mode more faster in transaction.